2013
DOI: 10.5348/ijcri-2013-03-284-cr-5
|View full text |Cite
|
Sign up to set email alerts
|

Strangulated incisional hernia after suprapubic catheter insertion: A case report

Abstract: Introduction: Hernia through the suprapubic catheterization site is extremely rare. Attention is required for such hernias as they can get easily complicated by obstruction and strangulation due to its narrow neck. These are lifethreatening complications. Case report: We report a case of a 65yearold man who presented with a strangulated incisional hernia through the SPC site. He was managed successfully by urgent surgical intervention. Conclusion: Incisional hernia through the suprapubic catheterization site s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Both of them underwent emergency abdominal repair without any bowel resection. However, in the case report by Harilingam et al, 5 the patient had an acute incarcerated and strangulated incisional hernia secondary to his previous suprapubic catheter. That patient subsequently had small bowel resection as part of his small bowel was found to be gangrenous.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Both of them underwent emergency abdominal repair without any bowel resection. However, in the case report by Harilingam et al, 5 the patient had an acute incarcerated and strangulated incisional hernia secondary to his previous suprapubic catheter. That patient subsequently had small bowel resection as part of his small bowel was found to be gangrenous.…”
Section: Discussionmentioning
confidence: 95%
“…As some authors in the previous papers have pointed out, incisional hernia secondary to suprapubic catheter should necessitate an urgent repair as the neck of the hernia tends to be narrow, and therefore it is prone to cause bowel obstruction which was seen in case reports by Rao et al, 3 Liu 4 and Harilingam et al 5 Of all known incisional herniae secondary to suprapubic catheters, only one patient did not have a repair as she was a palliative patient. Despite our patient being at a high risk, surgery to repair her incisional hernia was offered.…”
Section: Discussionmentioning
confidence: 99%
“…Once the distended bladder returned to pelvis, it provides an opportunity for the peritoneal contents to herniate through the potential weakness of the trocar site. 7 Harlingam et al 8 reported a case of strangulated incisional hernia after SPC. But in our cases, both were uncomplicated hernias with sac lying very close to fibrosed SPC tract and adhered to it.…”
Section: Spc Site Herniamentioning
confidence: 99%
“…Harilingam et al reported a case of strangulated hernia following trocar SPC done 2 years back in a 65 years male with urethral stricture following transurethral resection of prostate done 4 years back. 6 Lobel published 2 case reports of incisional hernia formation following SPC, one having a Burch urethropexy and second following vesicovaginal fistula repair. 7 Mehta et al, Rao et al and Mohammad hosseini, each published a single case experience.…”
Section: Introductionmentioning
confidence: 99%